TRADISI MAHAR DI RANAH LOKALITAS UMAT ISLAM: MAHAR DAN STRUKTUR SOSIAL DI MASYARAKAT MUSLIM INDONESIA - Noryamin Aini (Universitas Islam Negeri Jakarta, 2014)
Mahar Tradition in Muslim Locality: Mahar and Social Structure in Indonesian Muslim Society. Law consists of two fundamentals: moral and formal dimensions. Muslim legal scholars greatly appreciate the interplay of both aspects. Legal positivism separates them and law is ultimately framed in a formal-standard logical construct. Legal moral values are universal. It is flexible, universal and can be easily adapted into local contexts. Sociologically, social and cultural structure has proven to play an important role in the structuring of legal format. This paper proves that the practice of dower in a number of Muslim societies changes and varies crossing local boundaries. The dower tradition has been changed from money and other practical objects, into more symbolic materials, namely accessories and religious symbols.DOI: 10.15408/ajis.v14i1.1239